Emerging roles for methionine metabolism in immune cell fate and function - Liu, Shaojuan; Tang, Xiaotian; Huang, Min; Tang, Jianian; Yang, Yiwen (Frontiers in Immunology, 2025)
Metabolic reprogramming is a critical characteristic essential for the activation of immune cells. The altered amino acid metabolism, particularly changes in methionine metabolism, holds significant importance in directing the fate and function of diverse immune cells. Here we summarize the main transport system and metabolic pathway of methionine in immune cells, and the well-established and novel research findings of methionine metabolism-dependent modulation on major immune cell lineages and cancer cells are provided afterward. Unraveling the potential regulatory mechanism of methionine metabolism reprogramming in immune cells provides the new strategies for the therapy of autoimmune diseases and cancers.